Hematological Profiles and Alkaline Phosphatase Enzyme of Tissues in Male Mice Treated with Nifedipine Medication (Institute of Medico-legal Publications Pvt Ltd, 2021)
It is well recognized that certain types of medications for treatment of antihypertensive , known as Calciumchannel blockers (CCBs) and calcium ion antagonists are two types of calcium ion antagonists., only workby blocking the free passage of Ca+. Nifedipine, amlodipine, felodipine, diltiazem, and other medicationsare among them..Fifteen Adult male mice weighing 180-250 gm were randomly divided into three groupsand housed at the College of Science’s animal house, where they were fed a regular mice diet of water andpellets ad libitum.. Tthe control group (n=5) were treated with 1ml of distilled water, the 2nd group (n=5)were treated orally with 20 mg/kg body weight of Nifedipine while the 3rd group (n=5) were treated orallywith 60mg/kg by oral gavage for 35 days body weight of Nifedipine. The treatment was discontinued for 24hours before the animals were sacrificed..The data indicated biochemical parameters alkaline phosphatase (ALP) were found nonsignificantincreased in kidney and testicular tissues,but hematological parameters no any variance has been shownin both Hb,PCV,RBC, HCT, MCV, RDW and platelets in all test groups, whereas MCHC did show majorincreases in both dosage groups of nifedipine, but WBCs count data suggested a decrease in 20mg/Kgdosage only.We showed that nifedipine could reduce lymphocyte counts Substantial increases in monocyteand neutrophil counts were achieved at doses of 60 mg/kg BW when compared to the control group, andsignificant increases in monocyte and neutrophil counts were achieved at doses of 20 BW when comparedto the control group.,Above results indicate that the variations caused by nifedipine drug can have slightnegative effects on the parameters of kidney, testis enzymes and hematological parameters.